Modelling Organs, Tissues, Cells and Devices Using MATLAB and COMSOL Multiphysics - Dokos, Socrates; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book presents a theoretical and practical overview of computational modeling in bioengineering, focusing on a range of applications including electrical stimulation of neural and cardiac tissue, implantable drug delivery, cancer therapy, biomechanics, cardiovascular dynamics, as well as fluid-structure interaction for modelling of organs, tissues, cells and devices. It covers the basic principles of modeling and simulation with ordinary and partial differential equations using MATLAB and COMSOL Multiphysics numerical software. The target audience primarily comprises postgraduate students and researchers, but the book may also be beneficial for practitioners in the medical device industry.
Introduction to Modelling in Bioengineering -- Lumped Parameter Modelling with Ordinary Differential Equations -- Numerical Integration of Ordinary Differential Equations -- Distributed Systems Modelling with Partial Differential Equations -- The Finite Element Method -- Modelling Electrical Stimulation of Tissue -- Models of Diffusion and Heat Transfer -- Solid Mechanics -- Fluid Mechanics.
Keywords: Biomedical engineering; Mathematical models; Surgery; Computer software; Biomedical Engineering and Bioengineering; Mathematical Modeling and Industrial Mathematics; Surgery; Mathematical Software